The Influence of Budget Participation, Budget Goals Clarity and Internal Control Systems Implementation on Local Government Performance - Hutama, Rifqi Subhanullah; Yudianto, Ivan (Journal of Accounting Auditing and Business, 2019)
This study aims to examine the influence of budget participation, clarity of budget goals, and internal control systems on the performance of local government. This research was conducted on 31 regional work units in Karawang Regency. The study used a verification method with a quantitative approach. Data was collected through questionnaires instrument. The study employed path analysis. The results indicate that budget participation, budget goals clarity and the internal control system implementation simultaneously have a positive influence on the Government of Karawang Regency performance with the contribution of the influence that is equal to 73.4%. Partially, budgetary participation has a positive effect with a contribution of 24.3% influence, budget goals clarity has a positive effect on the contribution of the influence of 20.3%, and the control system implementation has a positive effect on the contribution of the influence of 28.8% on the Government of Karawang Regency.